Reviews of new publications - Holmes, Derek A (KUKILA, 1992)
Salathe, T. (ed). 1991. Conserving migratory birds ICBP Tech. Publ. No. 12, Cambridge, UK.The Hong Kong Bird Report 1990. The Hong Kong Birdwatching Society, GPO Box 12460,Hong Kong.